2-Iminobiotin Superimposed on Hypothermia Protects Human Neuronal Cells from Hypoxia-Induced Cell Damage: An in Vitro Study - Zitta, Karina; Peeters-Scholte, Cacha; Sommer, Lena; Gruenewald, Matthias; Hummitzsch, Lars; Parczany, Kerstin; Steinfath, Markus; Albrecht, Martin (Frontiers in Pharmacology, 2018)
Perinatal asphyxia represents one of the major causes of neonatal morbidity and mortality. Hypothermia is currently the only established treatment for hypoxic-ischemic encephalopathy (HIE), but additional pharmacological strategies are being explored to further reduce the damage after perinatal asphyxia. The aim of this study was to evaluate whether 2-iminobiotin (2-IB) superimposed on hypothermia has the potential to attenuate hypoxia-induced injury of neuronal cells. In vitro hypoxia was induced for 7h in neuronal IMR-32 cell cultures. Afterwards, all cultures were subjected to 25h of hypothermia (33.5°C), and incubated with vehicle or 2-IB (10, 30, 50, 100 and 300ng/ml). Cell morphology was evaluated by brightfield microscopy. Cell damage was analyzed by LDH assay. Production of reactive oxygen species (ROS) was measured using fluorometric assays. Western blotting for PARP, caspase-3, and the phosphorylated forms of akt and erk1/2 was conducted. To evaluate early apoptotic events and signaling, cell protein was isolated 4h post-hypoxia and human apoptosis proteome profiler arrays were performed. 25h after the hypoxic insult, clear morphological signs of cell damage were visible and significant LDH release as well as ROS production were observed even under hypothermic conditions. Post-hypoxic application of 2-IB (10ng/ml and 30ng/ml) reduced the hypoxia-induced LDH release but not ROS production. Phosphorylation of erk1/2 was significantly increased after hypoxia, while phosphorylation of akt, protein expression of caspase-3 and cleavage of PARP were only slightly increased. Addition of 2-IB did not affect any of the investigated proteins. Apoptosis proteome profiler arrays performed with cellular protein obtained 4h after hypoxia revealed that post-hypoxic application of 2-IB resulted in a ≥25% down regulation of 10/35 apoptosis-related proteins: Bad, Bax, Bcl-2, cleaved Caspase-3, TRAILR1, TRAILR2, PON2, p21, p27and phospho Rad17. In summary, addition of 2-IB during hypothermia is able to attenuate hypoxia-induced neuronal cell damage in vitro. Combination treatment of hypothermia with 2-IB could be a promising strategy to reduce hypoxia-induced neuronal cell damage and should be considered in further animal and clinical studies.